Penanda pragmatis dan peristiwa di kolom komentar akun media sosial instagram asli suroboyo pada kebiasaan baru wabah omicron di PPKM level 3 - Anggraeni, Nuni (Universitas Lampung, 2023)
This study aims to reveal pragmatic markers and events in the comments column of Asli Suroboyo's Instagram social media account that cause new habits in PPKM level 3 information. Using structural semiotics, this study shows that: (1) image uploads that use text elements, to interpret the relationship between verbal and visual signs, and; (2) Comment uploads showing information on the impact of PPKM level 3 felt by the community Instagram account in the field of education. From the sampling process, the object of research was obtained as many as 19 uploads of comments in the realm of education which can be categorized into three, namely: speech, information and opinion. Keywords: Instagram, Pragmatic Markers, Structural Semiotics